Characterization of silver nanoparticles and evaluation of their antimicrobial effect on Salmonella (Research, Society and Development, 2020)
Currently, the success of nanotechnology affects several areas of science, medicine, technology and, especially, the food industry. Silver nanoparticles (Ag-NPs) stand out, with their antimicrobial effect. Salmonella is a cause of foodborne diseases and there are reports of resistant serotypes. The use of Ag-NPs is an alternative for bacterial control in foods. The aim of this study was synthesize, characterize and verify the antimicrobial activity of Ag-NPs on serotypes of Salmonella. The  size of Ag-NPs was estimated and it was possible to detect two populations of 4.7 ± 0.09 and 35.7 ± 2.12. The zeta potential was -33.7 ± 11.8 mV indicating good dispersion stability.Ag-NP antimicrobial activity was determined from minimum inhibitory concentration (MIC).The lowest MIC found was 4.7 μg·mL-1 for Salmonella Enteritidis and the highest was 27.7 μg·mL-1 for Salmonella Infantis 1 isolate.The use of Ag-NPs is promising with respect to antimicrobial activity, however, improvements in synthesis methods should be explored in order to make commercial use viable.